2002
DOI: 10.1001/archneur.59.5.835
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging in Multiple-System Atrophy and Parkinson Disease

Abstract: Since several features on brain MR imaging are seen only in MSA-P, a simple diagnostic algorithm may improve the MR imaging diagnosis of MSA-P and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
110
2
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 23 publications
8
110
2
9
Order By: Relevance
“…The only exception was the midbrain area that was significantly different, with MSA-c showing lower values than MSA-p (p<0.01). In MSA-p cases, the measurements performed were not statistically satisfactory to differentiate from other parkinsonian patients, which is compatible with other studies [15][16][17] . Thus, MRI measures did not contribute for the differential diagnosis between MSA-c and other parkinsonian syndromes.…”
Section: Discussionsupporting
confidence: 88%
“…The only exception was the midbrain area that was significantly different, with MSA-c showing lower values than MSA-p (p<0.01). In MSA-p cases, the measurements performed were not statistically satisfactory to differentiate from other parkinsonian patients, which is compatible with other studies [15][16][17] . Thus, MRI measures did not contribute for the differential diagnosis between MSA-c and other parkinsonian syndromes.…”
Section: Discussionsupporting
confidence: 88%
“…This pattern of hypointensity has often been described as a marker of the parkinsonian variant of multiple system atrophy (MSA-P; 30) Kraft et al compared the frequency and specificity of T 2 putaminal hypointensity among PD, MSA-P, and progressive supranuclear palsy, finding that it occurred in each patient group and was not specific to MSA-P (31). Bhattacharya et al found putaminal hypointensity in both PD and MSA-P, but it was rated as milder in the PD patients (30). Putaminal hypointensity was the most sensitive but least specific parameter distinguishing MSA-P, with no significant difference between PD and MSA-P (32).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Hyperintensities in the pons, middle cerebellar peduncles, and cerebellum, corresponding to pontocerebellar tract atrophy and hyper-and/or hypointensities associated with posterior putaminal atrophy on T2-weighted images, have been described as characteristic findings on MR images in patients with MSA. [7][8][9][10][11][12] Diffusion-weighted MR imaging (DWI) has emerged as a useful method for detecting early pathologic changes of various diseases based on water diffusivity. 13 Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values have been used to evaluate the degree of tissue degeneration in various disorders.…”
mentioning
confidence: 99%